The effect of industrial structure adjustment and economic development quality on transitional China’s urban‒rural income inequity - Jiang, Tianhe; Han, Jun (Frontiers in Environmental Science, 2023)
Industrial structure adjustment is one of the key impetuses for China's transition to high-quality economic development, influencing urban-rural income equity through resource reallocation. This paper presents a theoretical analysis of the impact of industrial structure adjustment and economic development quality on the urban-rural income gap. A spatial dynamic model is adopted to analyse the influence of the industrial structure adjustment range, adjustment quality and economic development quality on the urban-rural income gap. The results based on full sample analysis suggest that the influence of the industrial structure adjustment range on the urban-rural income gap is not significant, while the quality of industrial structure adjustment is significantly positively correlated with the urban-rural income gap; the quality of economic development suppresses the income gap between urban and rural areas. The findings from regional analysis indicate that industrial structure adjustment and the quality of economic development have significantly heterogeneous effects in the eastern, central and western regions. Further analysis reveals threshold effects for both industrial structure adjustment and economic development quality on the urban-rural income gap. Given this, policy implications for a fairer development transition are noted based on an interpretation of the empirical results.